Acute Leriche Syndrome in Pancreatic Adenocarcinoma: A Case Report - Mosa, Eftychia; Manouvelou, Stamo; Tolia, Maria; Tsoukalas, Nikolaos; Ardavanis, Alexandros; Stasinopoulou, Myrsini; Kyrgias, George; Tavernaraki, Aggeliki (Current Medical Imaging, 2020)
Introduction: Coexistance of pancreatic carcinoma and Leriche syndrome is an extremely rare pathological condition. Leriche syndrome is defined as occlusion of the distal aorta at the bifurcation into the common iliac arteries. Case Report: We report the case of a 57-year old male patient with a locally advanced pancreatic tumor that during chemotherapy presented Leriche syndrome. Four months after the diagnosis and although the initial staging by MRI had only revealed a few atheromatic lesions of the abdominal aorta, the patient complained about claudication of the legs and hypoesthesia. Angiography with multi-detector computed tomography (MDCTA) was performed using aortography protocol and three-dimensional reconstruction of the images followed, demonstrating the relationship between pancreatic carcinoma and Leriche syndrome. Conclusion: Review of the literature revealed that acute abdominal thrombosis is rare in cancer patients. To our knowledge, complete occlusion of the aorta in a patient with pancreatic cancer has not been reported yet.
Keywords: leriche syndrome